Nilai-Nilai Karakter Remaja Muslim dalam Novel Merindu Baginda Nabi Karya Habiburrahman El Shirazy - Aisah, Iis; Hasanudin, Hasanudin; Sulaeman, Tatang (Bestari | Jurnal Studi Pendidikan Islam, 2020)
This study aims (1) to determine the character values ​​of Muslim teenagers in the novel Merindu Baginda Nabi by Habiburrahman El-Shirazy. (2) To determine the relevance of the character values ​​of Muslim teenagers in the novel Merindu Baginda Nabi by Habiburrahman El-Shirazy with current Islamic education. The research method used is library research. Literature study is a series of activities relating to methods of collecting library data, reading and taking notes and processing research materials. Meanwhile, the data sources obtained from the author's research are primary data from Merindu Baginda Nabi book and secondary data from other supporting books related to the research content. After analyzing the data, the authors obtained the following research results: The character values ​​of Muslim teenagers in the novel Merindu Baginda Nabi by Habiburrahman El Shirazy include: (a) characters towards Allah and Rasulullah include: loving Allah and Rasulullah Saw; shahihul worship (true worship; and love the mosque (b) character towards oneself including mujahidatun linafsihi (can fight against lust); haritsun a'la waqithi (time management/good management); respect for achievement; always say good; always try seeking knowledge; broad-minded; honest (c) character towards family and environment including: tolerance; mathnul khuluk (strong character); beneficial to others; responsible; good at maintaining Islamic brotherhood. Meanwhile, the relevance of youth character values Muslims in the novel Merindu Baginda Nabi by Habiburrahman El Shirazy with the values ​​of Islamic Education at this time are in accordance with KI and KD of Islamic Religious Education, namely practicing honest behavior or character, discipline, responsibility, care (mutual cooperation, cooperation, tolerance, peace ), polite, responsive and pro-active and show an attitude as part of the solution to various problems in interaction effectively with the social environment.